A Multiple Analysis Study of Sri Lankan Tamil Students’ Academic Success: Considering Family Support, Teachers’ Guidance and Self- Esteem - Krishnasamy Iynkaran (University of Jaffna, 2014)
Academic success is getting far more important in Sri Lankan Tamil society. Parents and teachers are trying for better educational achievement of Tamil students. Most of the students are blaming their parents and teachers for their failure in academic progress. Students’ self-esteem levels have also been a serious concern in academic achievement in many areas of research. Therefore this study was designed to determine the relationship between academic achievements considering with family support, teachers’ guidance and self esteem. Qualitative and Quantitative methods were used to collect appropriate data for this study. 96 samples were selected for this study and conducted self esteem scale test also. This study applied multiple analyses as its methodology. The study reveals that, importantly 100% of students have a perception that self-esteem is a deciding factor for their academic success. %). Gender different also is a value factoring in self-esteem level in Tamil society. As a main finding of this research is that, students’ level of self- esteem has to be building up because only 9% has high self-esteem in the universities. As far as other researchers found it will help them not only for their academic success but also for their personal life development. This research explores to find new ideas in creating suitable methods for Tamil students’ academic achievement in psychological and sociological manner. This study shall greatly help parents and teachers of Tamil students to understand the importance of self –esteem in academic performance, and endeavour should contribute to Tamil parents and teachers in getting to know the level of self esteem of Tamil students and can help to build up this to a required le
Keywords: Academic success; Family support; Teachers’ guidance; Self esteem; Educational Achieve ments and tamil students